(untitled) (Journal of the College of Basic Education, 2022)
Art remained, for a long time, besieged by the constraints of reality and the visual system, floundering in its circle, borrowing from it, and through the tendencies, ideas, and obsessions of the artist’s struggles with himself and his surroundings.The artist of light painting sought to express a new world full of rapid variables with a fast pace, and this appears clearly in their works through the adaptation of shapes, so they resorted, through their expressions, to the use of many plastic media in an effort to confirm expressive plastic values ​​linked to concepts specific to the era and the society around them. And the extent of what they think about and what they were influenced by from these technologies, to confirm their different artistic vision from previous trends.